Cyclic Nitronates via Sugar‐Derived Nitroalkenes in a Hetero‐Diels‐Alder/[3,3]‐Sigmatropic Rearrangement Pathway. - Vázquez, Darián (2024)
Diels-Alder betweennitroalkenes derived from a sugar scaffold and cyclopentadiene were examined.Depending on chemical structure of nitroalkene and polarity of solvent used,the reaction proceeded via the formation of a nitronate intermediate. Cyclicnitronates highly functionalized were obtained as chemically stable andstereochemically pure compounds. [3,3] sigmatropic shift of these onesafforded the Diels Alder cycloadducts in quantitative yield. Mechanisticaspects of reaction between nitroalkenes and cyclopentadiene has been studiedusing DFT computational methods. Nitronate derivatives are attractiveintermediates and open the way for the construction of valuable compounds withpotential applications.